(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Iron deficiency (ID) remains the most prevalent micronutrient disorder worldwide, with latent iron deficiency occurring significantly more often than clinically manifest iron deficiency anemia (IDA). In routine clinical practice, diagnosis is often limited to measuring hemoglobin (Hb) concentration, which leads to late detection of the condition. The aim of this work is to substantiate the clinical and economic feasibility of using a combined assessment of erythrocyte indices (MCV, MCH, RDW) for the early diagnosis of iron deficiency in the Republic of Uzbekistan.